Evaluation of Pharyngeal Clinical Changes after Palatine Tonsillectomy in Children - العلوني, فايز; ابراهيم, مصطفى; الحمصي, آية (Latakia University Journal -Medical Sciences Series, 2021)
The palatine tonsillectomy is currently one of the most common surgical procedures in the department of otolaryngology, but the follow-up of patients is often limited to the short postoperative period (only the first two weeks). However, the operation has long-term complications that appear from a period of one month or more in the form of chronic pharyngitis and the consequent unpleasant symptoms that affect the quality of life, and the occurrence of disturbances in taste such as the sense of a metallic taste or bitterness as a result of injury to the glossopharyngeal nerve that has a close anatomical relationship with the amygdala analgesic. Burns and soft tissue injury and the resulting scarring and stenosis of the nasopharynx and oropharynx, sap of the palate, the occurrence of strangulation in the voice, etc. Based on international studies, it was found that pharyngeal clinical changes are common in adults aged between 18-40 years, and this prompted us to question the possibility of their occurrence in children at younger ages. Main goal: A study of the pharyngeal clinical manifestations after tonsillectomy in children aged 5-18. And collecting patients' self-complaints, and assessing the clinical condition of the pharynx through clinical examination. Reducing the risks of random removal of tonsils, and thus reducing the economic cost.